Deterioration of the Hanson Logboat: chemical and imaging assessment with removal of polyethylene glycol conserving agent. Issue 1 (December 2017) - Pinder, Adam; Panter, Ian; Abbott, Geoffrey; Keely, Brendan
Abstract The state of preservation of wood in two samples from the Hanson Logboat, currently on display in Derby Museum and Art Gallery, was analysed using elemental analysis (EA), pyrolysis–gas chromatography/flame ionisation detection (Py-GC/FID), pyrolysis–gas chromatography/mass spectrometry (Py–GC/MS) and scanning electron microscopy (SEM). The samples were collected in 2003, after the boat had undergone conservation, and in 2011 after the condition of the boat began to deteriorate. Solvent extraction enabled removal of polyethylene glycol, with which the wood had been impregnated during conservation, allowing the degradation of the cellulose and lignin polymeric components of the woods to be assessed. Elemental compositions (C, H, N, O, S), Py–GC/FID, Py-GC/MS and SEM imaging reveal extensive degradation of the wood polymers during the eight year period since conservation.